Intellectual Jewels of the Nation: An Exploratory Study of Filipiniana Special Materials. Issue 3 (2nd July 2020) - Flores, Roana Marie L.
ABSTRACT: This paper aims to explore the cornucopia of special materials in the National Library of the Philippines' (NLP) Filipiniana Division (FD) of which has an intrinsic value in the Philippine history and culture. This study employs a descriptive qualitative research design using a structured interview as the main research method, further supplemented by public documents and statistical data from various divisions and sections of the NLP. The diversity of special materials housed in the FD complements the varied needs of the public and mirrors the uniqueness of the Philippine culture. The strength of these materials lies beyond its immense quantity – it is an intellectual jewel of the nation, waiting to be rediscovered by its people. The NLP has a bulk of special materials and dealing with it requires devoted time, restructured knowledge and perseverance which again poses another challenge to be confronted. As what one of the informants said '… one lifetime is not enough to organise them all [pertaining to the Philippine Insurgent Records and the Manuel L. Quezon Collection], ' therefore, mechanisms and processes should be clearly defined, recreated, streamlined and implemented in a sustainable manner to resolve the issues.